PENGARUH GAYA KEPEMIMPINAN DAN KOMPETENSI TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA KESEKRETARIATAN KEMENTERIAN PEMUDA DAN OLAHRAGA - Hizkia Hizkia; Zahera Mega Utama; Jubery Marwan (KELOLA: Jurnal Ilmiah Manajemen, 2022)
This study aims: 1) To determine the effect of leadership style and competence on the work effectiveness of employees at the Secretariat of the Ministry of Youth and Sports, 2) To determine the effect of leadership style on the work effectiveness of employees at the Secretariat of the Ministry of Youth and Sports, 3) To determine the effect of competence on effectiveness employee at the Secretariat of the Ministry of Youth and Sports. The research method used is a quantitative method using a questionnaire as a tool for data collection. The samples taken were echelon III and IV employees at the Secretariat of the Ministry of Youth and Sports as many as 51 people from a population of 51 employees. The results of the analysis of the magnitude of the influence of leadership style on employee performance is that there is an influence of leadership style on employee performance. This shows that 54.5% of employee performance variables are determined by leadership style variables, the magnitude of the influence of competence on employee performance is that there is an influence of competence on employee performance. This shows that 79.2% of employee performance variables are determined by the competence variable factor. While the influence of leadership style and competence on employee performance is the influence of leadership style and competence on employee performance. This shows that 79.2% of employee performance variables are determined by leadership style and competence variables.